Factors affecting wearable ECG device adoption by general practitioners for atrial fibrillation screening: cross-sectional study - Yao, Yi; Li, Zhichao; He, Yi; Zhang, Yalin; Guo, Zhaoxia; Lei, Yi; Zhao, Qian; Li, Dongze; Zhang, Zhi; Zhang, Yonggang; Liao, Xiaoyang (Frontiers in Public Health, 2023)
Introduction Atrial fibrillation (AF) is a challenging cardiovascular disease worldwide. Wearable electrocardiograph devices (WEDs) have great potential to improve the detection rate of AF in primary care. However, the factors that influence general practitioners’ (GPs) perception and acceptance of WEDs are not well understood. To identify factors that influence the intention of GPs to utilize WEDs in a clinical setting to screen patients for AF. Method The research hypotheses and questionnaire items were designed and developed based on the unified theory of acceptance and technology (UTAUT) framework. We used stratified sampling and obtained the data through an online survey. Structural equation modeling was used to analyze the collected data.Results: A total of 1,004 valid questionnaires from GPs across Sichuan province in China were collected. Three factors increased GPs’ intention to utilize WEDs to screen patients for AF, including performance expectancy (β = 0.121, p = 0.004), social influence (β = 0.356, p < 0.001), and price perception (β = 0.587, p < 0.001). Perception risk (β = −0.059, p < 0.001) decreased usage intention, while effort expectancy (β = −0.079, p = 0.155) and facilitating conditions (β = −0.014, p = 0.868) did not affect usage intention. Gender (β = −0.022, p = 0.179), age (β = 0.006, p = 0.699), education level (β = −0.22, p = 0.184) and training (β = 0.007, p = 0.69) were not significantly correlated with usage intention, and these four factors had no moderating effect on the path coefficients. Discussion GPs’ intention to utilize WEDs is affected by performance expectancy, price perception, perception risk and social influence. Researcher should improve the usability and perception of WEDs for screening and carry out studies to provide high-quality evidence for the security and efficacy of wearable devices.